Protein–ligand interactions investigated by thermal shift assays (TSA) and dual polarization interferometry (DPI) - Grøftehauge, Morten K.; Hajizadeh, Nelly R.; Swann, Marcus J.; Pohl, Ehmke (Acta crystallographica . Section D, Biological crystallography, 2015)
Over the last decades, a wide range of biophysical techniques investigating protein-ligand interactions have become indispensable tools to complement high-resolution crystal structure determinations. Current approaches in solution range from high-throughput-capable methods such as thermal shift assays (TSA) to highly accurate techniques including microscale thermophoresis (MST) and isothermal titration calorimetry (ITC) that can provide a full thermodynamic description of binding events. Surface-based methods such as surface plasmon resonance (SPR) and dual polarization interferometry (DPI) allow real-time measurements and can provide kinetic parameters as well as binding constants. DPI provides additional spatial information about the binding event. Here, an account is presented of new developments and recent applications of TSA and DPI connected to crystallography.